2020
DOI: 10.1002/lpor.201900344
|View full text |Cite
|
Sign up to set email alerts
|

Optical Imaging of Coherent Molecular Rotors

Abstract: Short laser pulses are widely used for controlling molecular rotational degrees of freedom and inducing molecular alignment, orientation, unidirectional rotation, and other types of coherent rotational motion. To follow the ultrafast rotational dynamics in real time, several techniques for producing molecular movies have been proposed based on the Coulomb explosion of rotating molecules, or recovering molecular orientation from the angular distribution of high harmonics. The present work offers and demonstrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Apart from the experimental demonstration of a fundamental physical effect, the presented results have several practical aspects. Polarization drag measurements may be regarded as a new diagnostic method for characterizing molecular rotation and its relaxation, an addition to the continuously expanding toolbox (e.g., [55][56][57][58][59] to name just a few). In particular, the observed nonexponential decay of the drag angle reflects the inhibited relaxation rate of the fast spinning molecular superrotors and depicts their gradual thermalization over a long time-scale.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the experimental demonstration of a fundamental physical effect, the presented results have several practical aspects. Polarization drag measurements may be regarded as a new diagnostic method for characterizing molecular rotation and its relaxation, an addition to the continuously expanding toolbox (e.g., [55][56][57][58][59] to name just a few). In particular, the observed nonexponential decay of the drag angle reflects the inhibited relaxation rate of the fast spinning molecular superrotors and depicts their gradual thermalization over a long time-scale.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the PAF is composed of a vortex plate acting as a radial polarizer [25][26][27][28][29] and a linear polarizer. Recently, a similar PAF was successfully applied to imaging of coherent molecular rotors [20]. Qualitatively, given a circularly polarized light at the input plane, the electric field at an output plane can be determined with the help of Jones calculus [30].…”
Section: Qualitative Description -Planar Wave Casementioning
confidence: 99%
“…Here, we present a theoretical analysis of the recently demonstrated [20] purely optical approach allowing detecting the instantaneous orientation of the principal optical axes of laser-excited molecular gas. The approach relies on ultrafast birefringence measurement using delayed femtosecond probe pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Alignment dynamics of different systems with varying individual pulse parameter such as, effect of pulse intensity was studied for the iodobenzene molecule by Lotte Holmegaard et al 16 , and for the O 2 and N 2 molecules by P. Peng 17 . Jérémy Bert et al 18 illustrated the time-resolved rotational dynamics in CO 2 gas after excitation with a single linearly polarized laser pulse, and unidirectional molecular rotation induced by a pulse with twisted polarization. Kenta Mizuse et al 19 reported high-precision time-resolved Coulomb explosion imaging of the rotational wave packets induced by a polarization-skewed double-pulse to investigate the creation process and dynamics of the packets in N 2 molecules.…”
Section: Introductionmentioning
confidence: 99%